2019
DOI: 10.3389/fmicb.2019.02000
|View full text |Cite
|
Sign up to set email alerts
|

Conditions Under Which Glutathione Disrupts the Biofilms and Improves Antibiotic Efficacy of Both ESKAPE and Non-ESKAPE Species

Abstract: Bacterial antibiotic resistance has increased in recent decades, raising concerns in hospital and community settings. Novel, innovative strategies are needed to eradicate bacteria, particularly within biofilms, and diminish the likelihood of recurrence. In this study, we investigated whether glutathione (GSH) can act as a biofilm disruptor, and enhance antibiotic effectiveness against various bacterial pathogens. Biological levels (10 mM) of GSH did not have a significant effect in inhibiting growth or disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…We also found that diarrhea intervened by Folium sennae increased the expression of pathogenic bacteria such as Streptococcus and Mycoplasma in intestinal tract of mice. Streptococcus and Mycoplasma in biofilm growth phase are principally responsible for an array of infections within hospital and bacteria in the biofilm state could resist host immune response and triggers infection [24]. The mice were given oral intranasal Streptococcus pneumoniae and induced antigen-specific mucosal and systemic immune responses, which is closely related to the severity of diarrhea [25].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that diarrhea intervened by Folium sennae increased the expression of pathogenic bacteria such as Streptococcus and Mycoplasma in intestinal tract of mice. Streptococcus and Mycoplasma in biofilm growth phase are principally responsible for an array of infections within hospital and bacteria in the biofilm state could resist host immune response and triggers infection [24]. The mice were given oral intranasal Streptococcus pneumoniae and induced antigen-specific mucosal and systemic immune responses, which is closely related to the severity of diarrhea [25].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, exogenous GSH has been described in many studies to be capable of disrupting biofilms of various bacterial strains and improving antibiotic efficacy. The effects of GSH disruption of biofilms have been reported at high concentrations, ranging from 1 mM to 30 mM and for monomicrobial biofilms of P. aeruginosa , S. pyogenes , S. aureus , K. pneumoniae , Enterobacter sp., E. coli and A. baumannii , including clinical and multidrug resistant (MDR) strains [ [47] , [48] , [49] ]. Several studies also investigated the potential mode of action of exogenous GSH on biofilm disruption and the enhancement of antibiotic effectiveness, examining transcriptome changes [ 48 ] or the effect on MDR efflux pumps or beta-lactamase activity post-GSH treatment [ 49 ].…”
Section: Role Of Gsh In Biofilm Formation and Disruptionmentioning
confidence: 99%
“…These findings, however, should be examined prudently as GSH at high concentrations is highly acidic (i.e. 20 mM of GSH has a pH of 3.92 and 3.89 when dissolved in Luria Broth (LB) or Phosphate buffered saline (PBS) respectively) [ 3 , 47 ]. A study reported that 30 mM GSH at neutral pH of 7.2 did not decrease the viability of MDR A. baumannii biofilm (76–94%) whereas 30 mM GSH at unbuffered intrinsic pH significantly decreased biofilm viability (16–38%) [ 47 ].…”
Section: Role Of Gsh In Biofilm Formation and Disruptionmentioning
confidence: 99%
“…Streptococcus and Mycoplasma in biofilm growth phase are principally responsible for an array of infections within hospital and bacteria in the biofilm state could resist host immune response and triggers infection [29]. The mice were given oral intranasal Streptococcus pneumoniae and induced antigen-specific mucosal and systemic immune responses, which is closely related to the severity of diarrhea [30].…”
Section: Discussionmentioning
confidence: 99%